Iron deposits in post‐mortem brains of patients with neurodegenerative and cerebrovascular diseases: a semi‐quantitative 7.0 T magnetic resonance imaging study. (2nd April 2014) - De Reuck, J. L.; Deramecourt, V.; Auger, F.; Durieux, N.; Cordonnier, C.; Devos, D.; Defebvre, L.; Moreau, C.; Caparros‐Lefebvre, D.; Leys, D.; Maurage, C. A.; Pasquier, F.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Accumulation of iron (Fe) is often detected in brains of people suffering from neurodegenerative diseases. However, no studies have compared the Fe load between these disease entities. The present study investigates by T2*‐weighted gradient‐echo 7.0 T magnetic resonance imaging (MRI) the Fe content in post‐mortem brains with different neurodegenerative and cerebrovascular diseases. Methods One hundred and fifty‐two post‐mortem brains, composed of 46 with Alzheimer's disease (AD), 37 with frontotemporal lobar degeneration (FTLD), 11 with amyotrophic lateral sclerosis, 13 with Lewy body disease, 14 with progressive supranuclear palsy, 16 with vascular dementia (VaD) and 15 controls without a brain disease, were examined. The Fe load was determined semi‐quantitatively on T2*‐weighted MRI serial brain sections in the claustrum, caudate nucleus, putamen, globus pallidus, thalamus, subthalamic nucleus, hippocampus, mamillary body, lateral geniculate body, red nucleus, substantia nigra and dentate nucleus. The disease diagnosis was made on subsequent neuropathological examination. Results The Fe load was significantly increased in the claustrum, caudate nucleus and putamen of FTLD brains and to a lesser degree in the globus pallidus, thalamus and subthalamic nucleus. In the other neurodegenerative diseases no Fe accumulation was observed, except for a mild increase in the caudate nucleus of AD brains. In VaD brains no Fe increase was detected. Conclusions Only FTLD displays a significant Fe load, suggesting that impaired Fe homeostasis plays an important role in the pathogenesis of this heterogeneous disease entity.